2020
DOI: 10.1001/jamanetworkopen.2020.23926
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of US Hospital Episode Spending for Acute Inpatient Conditions After the Patient Protection and Affordable Care Act

Abstract: IMPORTANCE Under the Patient Protection and Affordable Care Act (ACA), US hospitals were exposed to a number of reforms intended to reduce spending, many of which, beginning in 2012, targeted acute care hospitals and often focused on specific diagnoses (eg, acute myocardial infarction, heart failure, and pneumonia) for Medicare patients. Other provisions enacted in the ACA and under budget sequestration (beginning in 2013) mandated Medicare fee cuts. OBJECTIVE To evaluate the association between the enactment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Future work should test new policy initiatives to augment the ACA to improve the quality of care received by the most vulnerable individuals, including social care and upstream initiatives . Our work builds on prior research by extending findings through 2016 with a DiD analysis and comprehensively examining a broad range of measures reflective of the functioning of the health care system including novel analyses of high-value and low-value care, patient experience, communication, access, utilization of pharmacy, preventive visits, and other measures.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should test new policy initiatives to augment the ACA to improve the quality of care received by the most vulnerable individuals, including social care and upstream initiatives . Our work builds on prior research by extending findings through 2016 with a DiD analysis and comprehensively examining a broad range of measures reflective of the functioning of the health care system including novel analyses of high-value and low-value care, patient experience, communication, access, utilization of pharmacy, preventive visits, and other measures.…”
Section: Discussionmentioning
confidence: 99%
“…We found that research on VBC has increased significantly over the last decade. A driving factor could be the increasing pressure on health systems with rising costs, e.g., higher procedure volumes in surgery that are not necessarily in combination with better outcomes [ 14 ]. Furthermore, digitalization in general as well as improved accessibility and availability of digital outcome measurement devices and thus more precise outcome measures (e.g., sensors measuring real world walking speed) could have led to an increase in VBC research, as these developments facilitate comparing costs to outcomes [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 For clinicians to navigate the shift toward new payment models, it is important to recognize how each of these elements-declining hospital admissions, spending per inpatient episode, and payment rates-affect spending trends for inpatient services and associated care. Previous articles on overall Medicare inpatient spending have examined inpatient stays alone 5 or focused mainly on spending per episode 6,7 without quantifying how these elements contributed to overall episode-related OBJECTIVE: To describe Medicare inpatient episode spending trends between 2009 and 2017 as inpatient use declined among traditional Medicare beneficiaries.…”
mentioning
confidence: 99%